Al-Othmani, Sa'ad Uddin. “Actions of the Prophet (PBUH) in Leadership (Imāmah): Methodological and Legislative Implications,” Year 6, Issue 24 (Spring 1422 AH/ 2001 CE), Pp. 11-54. - العثماني, سعد الدين (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2001)
Sa’ad al-Othman’s study divides actions of the Prophet (PBUH) into legislative and non-legislative actions, inferring this distinction from the Prophet’s consultation with his Companions on some decisions, occasions in which they offered proposals contrary to his opinion, their interpretation of some of his actions as geared towards temporary interests, and the Rashidun Caliphs’ review of some of the Prophet’s actions after his death. Al-Othman then describes the four features of leadership (imāmah) actions: legislative, executive, ijtihādī (intellectual reasoning), and actions in non-religious matters. He demonstrates the importance of Prophetic actions in leadership and their implications, and addresses the methodology of gradual deliverance of rulings, consideration of the different conditions of people, and urgent situations. His study concludes with an attempt to resolve problematic issues in fiqh and hadith related to actions of the Prophet.